THE EXPERIENCE OF THE DENTAL AREA IN THE CITIZEN WEEK - 1ST EDITION: EXPERIENCE REPORT (CIPEEX, 2022)
THE FOLLOWING TEXT REFERS TO AN EXPERIENCE REPORT ABOUT THE PERFORMANCE OF A GROUP OF ACADEMICS OF THE DENTISTRY COURSE IN THE UNIVERSITY EXTENSION PROJECT - CITIZEN WEEK - 1ST EDITION. THE EXTENSION AND COMMUNITY ACTION COORDINATION OF UNIEVANGLICA, DEVELOPED THE FIRST EDITION OF THE "CITIZEN WEEK" PROGRAM IN PARTNERSHIP WITH THE MUNICIPALITY OF ANÁPOLIS, THROUGH THE MUNICIPAL DEPARTMENT OF EDUCATION. THIS PROJECT TOOK PLACE DURING ONE WEEK WITH WORKSHOPS GIVEN BY UNIEVANGELICA TO THE SCHOOL STUDENTS, FAMILY MEMBERS AND SCHOOL STAFF. THE PROPOSED TOPICS WERE PEACE BUILDING IN SCHOOLS, INFORMATION ON THE HUMAN BODY, CREATION OF WEBSITES, CURRICULUM VITAE PREPARATION, ENTREPRENEURSHIP, PERSONAL FINANCES, MEDICINAL PLANTS AND EVEN WORKSHOPS ON FOOD AND REGIONAL MENU FOR THE MERENDEIRAS OF THE UNIT. THE COURSE OF DENTISTRY OF THE MENTIONED INSTITUTION, PARTICIPATED DURING A DAY, IN THE MORNING AND AFTERNOON PERIODS. THE CITIZEN WEEK EXTENSION PROJECT CONSOLIDATES THE SERVICE TO THE BROADER DEMANDS OF THE COMMUNITY AND CONTRIBUTES TO LOCAL AND REGIONAL SOCIAL DEVELOPMENT. SOME STUDENTS AND TEACHERS ATTENDED THE STUDENTS AND EMPLOYEES OF A MUNICIPAL SCHOOL, LOCATED IN THE PARK DISTRICT OF THE PYRENEES, IN THE CITY OF ANÁPOLIS. THE WORK CARRIED OUT UNDERWENT AN EXCHANGE OF VALUES €‹€‹BETWEEN THE UNIVERSITY AND THE COMMUNITY, WHICH CONTRIBUTES TO THE COMPLETE FORMATION OF THE DENTIST-SURGEON, CRUCIAL FOR PUTTING KNOWLEDGE INTO PRACTICE IN NON-FORMAL AND DISTANT PLACES OF ACADEMIC REALITY.&NBSP;PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): DENTISTRY, DENTAL CARIES, DENTAL TRAUMA, HEALTH PROMOTION.&NBSP;